Helicobacter pylori in z njim povezane bolezni - Jeruc, Jera (Medicinski razgledi, 2010)
Helicobacter pylori, a spiral shaped pathogenic bacterium, was first isolated by Barry Warren and Robin Marshall about 20 years ago, earning them aNobel Prize in Physiology or Medicine in 2005. More than 50 % of the world population harbour Helicobacter pylori in their upper gastrointestinal tract and Helicobacter pylori infection is now accepted as the cause of the most common form of chronic gastritis. The prevalence of infection inversely correlates with socioeconomic status. When not treated, the infection will persist in the stomach of most people for decades, but as much as 80 % of infected individuals will never experience dinical symptoms despite having chronic gastritis. Histology shows active chronic inflammation with infiltration of the lamina propria by 1ymphocytes and p1asma cells, and infi1tration of the mucous neck region by neutrophils. Lymphoid follicles can develop, sometimes causing mucosa1 nodu1arity on endoscopy. Approximate1y 10-20% of those co1onized by Helicobacter pylori ultimately develop gastric and duodena1 ulcers. It is a1so widely accepted that the infection is the triggering factor for mu1tifoca1 atrophic gastritis and intestina1 metap1asia,i.e. the changes that increase the risk for the intestina1 type of gastric cancer. Helicobacter pylori has been classified as a type 1 (definite)carcinogen by the WHO. Furthermore, most ofthe gastric MALT 1ymphomas are associated with Helicobacter pylori infection. The diagnosis of Helicobacter pylori infection is based on methods requiring gastric mu cosa obtained by endoscopy (histo1ogy, rapid urease test, culture, polymerase chainreaction (peR or non-invasive methods (sero1ogy, urea breath test). Its therapy consists of a combination of proton-pump inhibitors and various antibiotics. Because of antimicrobia1 resistance, there are attempts to deve10p a vaccine that wou1d prevent infection with Helicobacter pylori.
Keywords: Helicobacter Infections; Peptični ulkus; Želodec, novotvorbe; Diagnosis; Limfom mieloidnega tkiva, povezani z sluznico; Therapy; prebavila; Pathology; želodec; Helicobacter Pylori; Gastritis; vnetja; Peptic Ulcer; epidemiologija; Stomach Neoplasms; zdravljenje; Lymphoma, Mucosa-Associated Lymphoid Tissue; Helicobacter, infekcije; diagnostika